The Effects of Hypnosis Relaxation Towards Fetus Heart Frequency and Vital Signs among Pregnant Women with Pre-eclampsia - Khuzaiyah, Siti; Anies, Anies; Wahyuni, Sri (IJNP (Indonesian Journal of Nursing Practices), 2020)
Background: One of the causes of Maternal Mortality Ratio (MMR) in Indonesia is pre-eclampsia. Mothers with pre-eclampsia disorder who are followed by anxiety tend to have specific vital sign change included increasing blood pressure, heart rate, respiratory rate, and fetus heart rate. Pregnant suffered pre-eclampsia should keep the balance of mind and emotion, as well as to reduce a complication of pre-eclampsia towards mothers and their fetus. Objective: The objective of this study was to analyze the effects of the relaxation hypnosis on fetus heart rate and vital signs of pregnant women with pre-eclampsia. Method: This study was a quasi-experiment with a pretest-posttest design. The total subjects were 32 pregnant women with pre-eclampsia, which selected by purposive sampling techniques. The researcher did hypnosis relaxation for three times. a Wilcoxon test was used to analyze the paired bivariate for systolic blood pressure, while the Mann-Whitney test and independent t-test were used to analyze fetus heart frequency.Result: This study shows that hypnosis relaxation can reduce the systole blood pressure (p-value = 0.000; CI=12.185-23.109), reduce diastole (p-value = 0.000; CI= 8.630 – 14.311), reduce heart rate (p value = 0,004; CI= 2.07 – 8.989) and reduce respiratory rate (p value = 0.000; CI = 2.785 – 6.275). In terms of the effect on the fetus, hypnosis relaxation affect the fetus heart rate (p value = 0,000; CI = 5.834 – 13.930). Conclusion: Hypnosis relaxation influences the change of fetal heart rate and vital signs of pregnant women with pre-eclampsia.